Implementasi Kurikulum Merdeka Berbasis Budaya Banjar dalam Meningkatkan Kesadaran Lingkungan Peserta Didik Sekolah Dasar - Nadilatu Zahwa; Nurriyanti; Seftiana Anindya Narfa; Salma Safitri; Diani Ayu Pratiwi; Aslamiah (Universitas Islam Nahdlatul Ulama Jepara, 2026)
The Merdeka Curriculum promotes contextual learning through the use of local culture as part of the learning process. However, the implementation of the Merdeka Curriculum that integrates Banjar culture to enhance elementary students' environmental awareness still requires further investigation. This study aims to describe the implementation of the Banjar culture-based Merdeka Curriculum in enhancing the environmental awareness of fourth-grade students at SDN Murung Raya 5. This study employed a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews with a purposively selected classroom teacher and documentation of the interview process. The findings show that the implementation of the Merdeka Curriculum was supported by the development of flexible teaching modules, the use of digital media such as Smart TVs and projectors, and diverse learning strategies to accommodate the needs of students with special educational needs. The integration of Banjar local wisdom was implemented through local language learning, the creation of traditional rhymes and poetry, and local food programs. Meanwhile, students' environmental awareness was developed through practical habituation programs, including Clean Saturday, Healthy Saturday, and waste-sorting habits. The findings imply that the use of local culture in learning can serve as a relevant strategy to support the strengthening of character education and environmental education in elementary schools.